STUDI PERTUMBUHAN NYAWAI (Ficus variegata Blume) DI KHDTK RIAM KIWA KALIMANTAN SELATAN - Farhan Aryo Wicaksono; Eny Dwi Pujawati; Damaris Payung (Jurnal Sylva Scienteae, 2020)
The increase of timber consumption by the industry is not balanced with the supply of raw materials which is precisely reduced in number. One of the types of alternative plants that can be utilized is Nyawai. This research aims to determine the variation of growth and percent of life of each family, in order to provide recommendations of the best families that are able to adapt in a KHDTK Riam Kiwa environment. This research uses Nyawai plant in forest area with special purpose (KHDTK) Riam Kiwa is 27 months old with 9 families from 3 different Provenans namely South Kalimantan, East Kalimantan and central Kalimantan with a planting distance of 3 m x 3 m. Based on measurements obtained by the result of the highest lifetime survival percentage of 27 months Nyawai which averages 96%, the average height is 5, 539 m, the average diameter of 9.9 cm and the average bar straightness 4.45.